Atividade discursiva na sala de aula: contribuições das perguntas dos estudantes naconstrução de conhecimento científico - Douglas Henrique de Mendonca (2010)
The problem that generates the research reported here is dedicated to understand the contributions that students questions bring up to the meaning making in the science classrooms. Working on the socio-cultural perspective founded by Vygotsky and Bakhtin we investigate particularly rich discursive classroom interactions iniciated by students genuine questions and their unfolding in one science classroom. We follow three research questions: 1st. which are the circumstances that foster students questions in science classrooms; 2nd. How the demands of students questioning relate to purposes and strategies adopted by the teacher; 3rd. which are the unfolding of students questions in the discursive events in a science classroom. The empirical evidences came from a teaching sequence that introduces chemical reaction model to a 8th grade class. The learning environment of this classroom is characterized by effective students participation in the construction of scientific concepts and by the disposition of the teacher in praising students contributions and perspectives. From our results, we detach e importance of questioning as a way of students collaborate and think together, with the teachers guide, about scientific concepts and issues, closing the gaps between science contents and meaningful contexts of life. Other contribution of students questioning is that it provides feedback to the teacher, allowing adjustments of the teaching explanatory structure to the interests, experiences and previous knowledge of the students. For this, the attentive listening is crucial for teachers to understand the students demands when they ask questions. We identified some characteristics of the learning environment, created by the teacher that favored the students to raise their questions dialogic teaching, thematic curriculum, diversification of activities, friendship, confidence and respect between the participants, and the preparation ofstudents, by previous activities, for discussion. We also confirm the results from Aguiar, Mortimer and Scott (2010) that both the communicative approach and the science contents of the lessons are not a single choice made by the teacher, but emerge, many times, from negotiation by teacher-students interactions.